Effects of cigarette smoke exposure on a mouse model of multiple sclerosis. (2022) - Ho, Jenny; Koshibu, Kyoko; Xia, Wenhao; Luettich, Karsta; Kondylis, Athanasios; Garcia, Llenalia; Phillips, Blaine; Peitsch, Manuel; Hoeng, Julia
Abstract: Multiple sclerosis (MS) is an inflammatory autoimmune disease associated with genetic and environmental factors. Cigarette smoking is harmful to health and may be one of the risk factors for MS. However, there have been no systematic investigations under controlled experimental conditions linking cigarette smoke (CS) and MS. The present study is the first inhalation study to correlate the pre-clinical and pathological manifestations affected by different doses of CS exposure in a mouse experimental autoimmune encephalomyelitis (EAE) model. Female C57BL/6 mice were whole-body exposed to either fresh air (sham) or three concentrations of CS from a reference cigarette (3R4F) for 2 weeks before and 4 weeks after EAE induction. The effects of exposure on body weight, clinical symptoms, spinal cord pathology, and serum biochemicals were then assessed. Exposure to low and medium concentrations of CS exacerbated the severity of symptoms and spinal cord pathology, while the high concentration had no effect relative to sham exposure in mice with EAE. Interestingly, the clinical chemistry parameters for metabolic profile as well as liver and renal function (e.g. triglycerides and creatinine levels, alkaline phosphatase activity) were lower in these mice than in naïve controls. Although the mouse EAE model does not fully recapitulate the pathology or symptoms of MS in humans, these findings largely corroborate previous epidemiological findings that exposure to CS can worsen the symptoms and pathology of MS. Furthermore, the study newly highlights the possible correlation of clinical chemistry findings such as metabolism and liver and renal function between MS patients and EAE mice. Highlights: Multiple sclerosis is an inflammatory autoimmune disease affected by many factors. First inhalation study to correlate the different doses of cigarette smoke on MS. Findings largely corroborate with previous epidemiological findings on CS exposure. High concentration of CS had no observable effect on EAE, contrast to low and medium. Potential correlation between MS and EAE model using clinical chemistry parameters.